Brief Report: Relationship Between ADOS-2, Module 4 Calibrated Severity Scores (CSS) and Social and Non-Social Standardized Assessment Measures in Adult Males with Autism Spectrum Disorder (ASD). - Morrier, Michael; Ousley, Opal; Caceres-Gamundi, Gabriella; Segall, Matthew; Cubells, Joseph; Young, Larry; Andari, Elissar (Journal of Autism & Developmental Disorders, 2017)
The ADOS-2 Modules 1-3 now include a standardized calibrated severity score (CSS) from 1 to 10 based on the overall total raw score. Subsequent research published CSS for Module 4 (Hus, Lord, Journal of Autism and Developmental Disorders 44(8):1996-2012, 2014); however more research is needed to examine the psychometric properties of this CSS. Forty males with ASD completed an assessment battery consisting of ADOS-2 Module 4 and other clinical measures assessing core ASD symptomology and comorbidity. Pearson correlation analyses found that CSS did not correlate with measures that assessed core social deficits of ASD or general psychiatric co-morbidity, but CSS did correlate negatively with intellectual quotient. These findings provide information on the limitations and relevance of CSS to be taken into account in future clinical evaluations of ASD.